Estudio de factibilidad para la implementación de un centro de acopio para el almacenamiento y conservación de mariscos, cantón Quevedo, año 2013 - Paéz Peredes, Cristina Emperatriz (2014)
Currently Quevedo, with great potential for productive and commercial activities with large and micro enterprises, dynamism and development based on their ability to market and make their trading activities of a wide range of products and by-products adequately meet demand generating local and regional jobs, economic benefits and improving the continued growth of microenterprises. This research was conducted with the main objective of implementing a storage facility for the storage and preservation of shellfish in the canton Quevedo, the same was to perform a market study, conduct a technical and economic study and finally determine the project profitability through financial evaluation. Furthermore, this project will have teams both material and human talent highly trained according to the requirements thereof, which will meet the needs of merchants and also generate income for further growth, the total investment of the same will be $ 59.573,51 funded 70% with the help of the National Finance Corporation and the remaining 30% equity. According to the results presented in the financial evaluation and by reference to a rate of 10% chance of a positive Net Present Value (NPV) of $ 3.353,58 was obtained above whose initial investment is recovered over a period of about 3 years. In relation to financial analysis, with a more representative parameter is the Internal Rate of Return (IRR) it yielded a result of 13%, which is above the 10% rate applied to the project opportunity, which indicates that the same is profitable. The Benefit Cost Ratio (RB/C) gave more than $ 1,29 units indicating that investment is feasible and can be run without any problem result.